2023
DOI: 10.1037/dhe0000215
|View full text |Cite
|
Sign up to set email alerts
|

Magnifying and healing colonial trauma in higher education: Persistent settler colonial dynamics at the Indigenizing university.

Abstract: Processes of Indigenization under way in Canada aim to bring more Indigenous students and faculty to mainstream colleges and universities. These Indigenization initiatives are critical components that work toward reconciling systemic and societal inequalities between Indigenous and non-Indigenous within higher education. Despite these important efforts, institutions of higher education were founded on and continue to reflect the goals and norms of a settler colonial society, and such contexts constitute a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Steinman and Sanchez [ 34 ] emphasize that the process of Indigenization – meaningful changes to practices and processes in universities to include Indigenous Peoples, and ways of knowing and doing things - must be done thoughtfully to minimize the re-creation of harm. If universities prioritize public and explicit changes, for example, celebrating the hiring of Indigenous faculty and incorporating Indigenous art into the environment, without deconstructing policy that upholds colonial power structures, this contradiction can perpetuate colonial power dynamics and harm to Indigenous Peoples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Steinman and Sanchez [ 34 ] emphasize that the process of Indigenization – meaningful changes to practices and processes in universities to include Indigenous Peoples, and ways of knowing and doing things - must be done thoughtfully to minimize the re-creation of harm. If universities prioritize public and explicit changes, for example, celebrating the hiring of Indigenous faculty and incorporating Indigenous art into the environment, without deconstructing policy that upholds colonial power structures, this contradiction can perpetuate colonial power dynamics and harm to Indigenous Peoples.…”
Section: Discussionmentioning
confidence: 99%
“…The students in this study identified several important ways that cultural incongruity can be reduced that is supported by literature and Indigenous leaders. The most important of these is hiring Indigenous faculty staff, and support services and ensuring they are included meaningfully in all aspects of the academic institution [ 34 , 35 ]. Indigenization in the university is not possible without Indigenous leadership and working partnership between Indigenous and non-Indigenous faculty and staff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Settler colonialism continues today and actively causes harm to many NA students (Masta, 2019; Steinman & Kovats Sánchez, 2021). Masta (2019) discussed three markers of ongoing settler colonialism in higher education.…”
Section: Na Students and Higher Educationmentioning
confidence: 99%